Sexual Health Education- Using Animated Videos to Teach Teenagers and Young Adults. (1st August 2022) - Anaemejeh, N; Bachmann, G; Hutchinson-Colas, J; Alshowaikh, K
ABSTRACT: Introduction: Sexual and reproductive health is an important determinant of overall wellness. Sexual health goes beyond preventing STI or unwanted pregnancy; rather, it improves the quality of life, promotes healthy relationships, and enhances positive body image. However, sexual education has been considered a taboo in most homes and cultures. Even among more liberal societies, it remains an uncomfortable discussion for most. Current formal sexual health curriculum are often inadequate and limited to topics such as STI prevention and contraception. Recently, the rise of social media and technology has increased accessibility to sexual education content. Adolescents are increasingly aware of the importance of normalizing discussions on sexual preparation. However, even with the increased awareness, there remains a challenge to provide quality and effective sexual health education. Parents and teachers may not feel adequately prepared to discuss the breadth of sexual health with teenagers and young adults. Using animated videos for education appear to be a powerful tool to increase knowledge and promote healthy discussions on this topic. Objective: The purpose of this review was to 1)investigate the current utilization of animated videos to teach sexual health topic, 2)analyze the effectiveness of using animated videos to teach this topic 3) Identify some current challenges to effective utilization and 4) propose some future trends and best practices for using these videos. Methods: Online databases including PubMed and google scholar were accessed, with search keywords "sexual health, " "animated videos, " "challenges" "web based teaching" Results: Animated videos can be helpful tools to supplement and enhance the traditional method of sexual health education. A few online platforms use animated videos to provide a comprehensive sexual health education. However, limited research is available on the effectiveness of incorporating this innovative, multimodal learning tool into sexual education curriculum. Using animated videos has been shown to improve adolescent knowledge by stimulating thoughts, feelings, concerns, and willingness to learn. Employing effective learning tools to communicate essential sexual health topics may reduce adolescent vulnerabality to sexual abuse, coercion, sexually transmitted infections and improve health and wellness. In addition, with increasing global accessibility to technology these videos can impact a large number of teenagers. Conclusions: Increased access to technology and digital media allows the health care team to incorporate creative methods in the provision of comprehensive sexual health education. Animated videos can be an effective method for teaching this topic by providing a fun and informative method of delivering vital information without the added discomfort that may be associated with traditional methods. This empowers teenagers and young adults to take control of their sexual health, become responsible and well informed adults and promote overall health and wellness. Disclosure: No